Pengaruh Profitabilitas, Likuiditas, Leverage, Sales Growth, dan Aktivitas Terhadap Financial Distress Pada Perusahaan Entertainment - Nilam Sabrina; Ihrom Caesar Ananta Putra; Wiwik Fitria Ningsih (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
The South Korean entertainment industry, particularly the K-Pop music sector, has become one of the drivers of the global creative economy. However, high market volatility and reliance on trends make entertainment companies vulnerable to financial distress. This study aims to analyze the influence of profitability, liquidity, leverage, sales growth, and activity on financial distress in South Korean entertainment companies listed on the Korea Exchange (KRX) from 2019 to 2023. The research method uses a quantitative approach with secondary data from the financial reports of 7 companies selected through purposive sampling from a total population of 51 companies. Data analysis includes descriptive statistical tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination analysis. The results show that partially, profitability, liquidity, and activity have a significant effect on financial distress, while leverage and sales growth do not have a significant effect. Simultaneously, all five variables together have a significant effect on financial distress.